Photophysical properties of safranine and phenosafranine. A comparative study by laser flash photolysis and laser induced optoacoustic spectroscopy - Broglia, Martin Federico (2005)
The triplet quantum yield of the dyes safranine and phenosafranine was determined in methanol and acetonitrile by laser flash photolysis (LFP) and laser induced opto-acoustic spectroscopy (LIOAS). The excited singlet properties of both dyes were also determined in the two solvents. The LFP determination of the triplet yield was carried out by actinometric determination of the product ΦTεT and independent estimation of εT by the singlet depletion method and by energy transfer using anthracene as energy donor. The results of the three methodologies coincide within the experimental error. The values of ΦT are in the range 0.21-0.50, and in the case of phenosafranine are considerably higher than those previously reported in the literature. An interesting outcome is that the results of LIOAS determination agree with those of LFP within the confidence interval.